2018
DOI: 10.1016/j.jcmg.2017.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of J-CTO Score Derived From Computed Tomography Versus Angiography to Predict Successful Percutaneous Coronary Intervention

Abstract: The CTA-derived J-CTO score was a more useful predictor of both procedural success and 30-min wire crossing than the J-CTO score derived from conventional angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 18 publications
0
35
4
Order By: Relevance
“…1). Notably, the trials on CTA-derived scoring systems comprised European, Japanese, and Chinese populations enrolled between 2007 and 2016, and predominantly focused on antegrade wiring strategies [25,27,29,30]. Hence, the clinical applicability of CT scores for prediction of CTO PCI success rates using retrograde wiring and dissection and re-entry strategies is largely unknown.…”
Section: Cta-derived Scores For Prediction Of Cto Pcimentioning
confidence: 99%
See 2 more Smart Citations
“…1). Notably, the trials on CTA-derived scoring systems comprised European, Japanese, and Chinese populations enrolled between 2007 and 2016, and predominantly focused on antegrade wiring strategies [25,27,29,30]. Hence, the clinical applicability of CT scores for prediction of CTO PCI success rates using retrograde wiring and dissection and re-entry strategies is largely unknown.…”
Section: Cta-derived Scores For Prediction Of Cto Pcimentioning
confidence: 99%
“…Notably, the CT-RECTOR score was externally validated in a Chinese population as a more accurate prediction rule for 30-min guidewire crossing and final procedural success rate as compared with the angiographic J-CTO (Multicenter Chronic Total Occlusion Registry of Japan) score [31]. Subsequently, two trials explored the predictive ability of the J-CTO score derived from CTA (the so-called J-CTOCT score) [29,30]. Interestingly, while in one study the non-invasive J-CTO score determined by CTA yielded a similar predictive value for 30-min guidewire crossing as compared with the angiographic J-CTO score [29], the other study demonstrated significantly higher discriminating accuracy of the J-CTOCT score than that of the angiography-based J-CTO score [30].…”
Section: Cta-derived Scores For Prediction Of Cto Pcimentioning
confidence: 99%
See 1 more Smart Citation
“…Coronary CT angiography (CCTA), a non-invasive imaging technique, can characterize the features of the CTO segment, which is a notable advantage over CA for the assessment of longer and more tortuous CTO lesions, as well as segments distal to a CTO lesion [11]. Moreover, it can provide prognostic information beyond CA [12][13][14][15][16][17], and it has been investigated as an alternative pre-procedural imaging method for CTO-PCI [18]. However, it is unclear whether the RECHARGE score can be calculated using CCTA data.…”
Section: Introductionmentioning
confidence: 99%
“…Further, success rates for coronary CTOPCI procedures in our study cohort cannot be ascertained for inpatient hospitalizations as well. Severity of the CTO lesion as measured by SYNTAX or J-CTO scoring system, both of which are good predictors of procedural success,[38] could not be determined in our study cohort. Finally, the NIS data are available for in-hospital stay only; as such differences in long term outcomes for patients undergoing single-vessel coronary CTO-PCI for stable CAD could not be assessed.…”
Section: Discussionmentioning
confidence: 99%